Prevalence of Autotrophy in Non-humic African Lakes - (:unkn) unknown (My University, 2022)
Heterotrophic respiration of organic matter (OM) is thought to dominate over aquatic primary production (PP) in most freshwater lake ecosystems. This paradigm implies that lateral transport of OM from the terrestrial biosphere subsidize the major fraction of aquatic respiration and that many lakes are a net source of carbon dioxide (CO2) to atmosphere. Nevertheless, African lakes were absent of the datasets upon which this paradigm was built. Here, we report a comprehensive and methodologically consistent data set of pelagic PP and community respiration (CR) obtained over the last decade in contrasting non-humic African lakes including 5 of the East African Great lakes (Tanganyika, Kivu, Edward, Albert, Victoria) and smaller shallow lakes located in Eastern Africa. Also, we determined the partial pressure of CO2 in surface waters and examined the sources and dynamics of organic and inorganic carbon by means of stable isotope tools across a wide range of physical and chemical conditions and productivity status. Our observations revealed that the threshold value at which the equivalence between PP and CR is met is substantially lower in Africa (10 mmol C m−3 d−1) than at higher latitude (25 mmol C m−3 d−1), suggesting that non-humic African lakes tend to be more autotrophic than expected from empirical relationships derived from data collected in boreal and temperate regions. Integrated at the regional scale, we estimate that PP is about 20 times higher than the organic carbon burial in sediments. It implies that a large fraction (< 90%) of PP is effectively recycled in the warm water column of non-humic African lakes.
Keywords: African Research